Detection of HPV subtypes by mass spectrometry in FFPE tissue specimens: a reliable tool for routine diagnostics - Kriegsmann, Mark; Kriegsmann, Katharina (Journal of clinical pathology, 2017)
Aims: Human papilloma virus (HPV) infection is a causative agent for approximately 5% of all new cancer cases in humans. The virus is detected in cervical, anal, vaginal, penile, vulvar and head and neck cancers and has prognostic implications. Thus, test systems are required to detect high-risk but also low-risk HPV subtypes with high specificity and sensitivity in a time-effective and cost-effective manner. In the present study we developed a new mass spectrometry (MS)-based test system for the detection of HPV infections in formalin-fixed paraffin-embedded (FFPE) tissue samples. Methods: A high-throughput matrix-assisted laser desorption ionisation time of flight MS-based assay was applied to genotype 19 HPV types in FFPE tissue specimens (n=46). The results from the MS assay were compared with the results obtained from two hybridisation-based test systems: the HPV 3.5 LCD-array kit and the EuroArrayHPV system. Results: In 36 out of 46 (78%) tissue samples, a HPV infection could be detected by the MS-based HPV assay. In 16 samples (44%) only one and in 20 samples (56%) two to six HPV subtypes were identified. The overall agreement of all three assays was almost perfect (Cohen's k value: 0.83). Conclusions: The MS-based assay is highly sensitive, reliable as well as cost-effective and represents a suitable technology for the detection of HPV infections in FFPE tissue material.
First published: 8 October 2016
Gesehen am 20.06.2018